Heavy Metal Concentration Level In Fiddler Crab (Uca Annulipes) And Soldier Crab (Dotilla Myctiroides) In Intertidal Areas Of The West Coast, Peninsular Malaysia - Mohammad, Mohad Ikram (2010)

(untitled)
The study investigated the distribution concentration levels of heavy metals Zn, Cu, Cd and Pb in Uca annulipes and Dotilla myctiroides crabs with addition to sediment samples that were collected from the intertidal areas of Selangor (5 sites) and Negeri Sembilan (3 sites), west coast of Peninsular Malaysia. The particle size distribution (clay, silt and sand fraction) and organic matter content in sediment samples collected were also determined because these factors can play important roles in influencing the heavy metals concentration level in crabs. The mean heavy metals concentration level (ug/g dry weight) in whole body of U. annulipes and D. myctiroides were found to range from 69.94 – 77.20, 45.81 – 104.93, 1.65 – 2.40 and 21.35 – 30.32 for Zn, Cu, Cd and Pb, respectively. The patterns of heavy metals distribution in both crab species of the different sampling stations were found to be {Cu > Zn} or {Zn > Cu} > Pb > Cd, where the highest were usually found for Zn and Cu which were not consistent in their order, and the lowest were found for Cd and Pb. This was explained due to the different function of heavy metals in crabs such as for essential purpose, sequestration and even to be excreted. As for sediments, the mean heavy metals concentration level (ug/g dry weight) were found to range from 7.26 – 47.59, 1.51 – 15.19, 0.11 – 0.37 and 5.83 – 47.59 for Zn, Cu, Cd and Pb, respectively. The present levels of heavy metals in sediments of the different sampling stations were found to be low when compared to few sediment quality guideline and background level, indicating the relatively uncontaminated metal pollution conditions in which crabs inhabited. A higher heavy metals concentration level was generally recorded in U. annulipes when compared to those of D. myctiroides. This difference was related to the particle size distribution and organic matter percentages (%) of the crab microhabitat sediment settings. Results showed that a significantly (p < 0.05) higher distribution of the fine particles (clay and silt) and organic matter content were found in sediments inhabited by U. annulipes when compared to those sediments inhabited by D. myctiroides which had significantly (p < 0.05) lower distribution. The fact that fine particles and organic matter of sediments have capability to bind heavy metals and crabs feed by scraping of surface sediments, hence the crabs potential to bioaccumulate heavy metals bonded onto fine particles and organic matter of sediments can assume to be higher for U. annulipes when compared to D. myctiroides. This therefore might explain the differences in heavy metals concentration level observed in U. annulipes and D. myctiroides which is much related to crabs preferences for different microhabitat sediment settings and daily crab activity of feeding. This ability of U. annulipes and D. myctiroides to bioaccumulate heavy metals from sediments may also be important in order to facilitate them as potential biomonitor organism for the monitoring of heavy metal pollution in the intertidal area of west Peninsular Malaysia.